Neutrophil–lymphocyte ratio and platelet–lymphocyte ratio as potential predictive markers of treatment response in cancer patients treated with immune checkpoint inhibitors: a systematic review and meta-analysis - Rugambwa, Tibera K.; Abdihamid, Omar; Zhang, Xiangyang; Peng, Yinghui; Cai, Changjing; Shen, Hong; Zeng, Shan; Qiu, Wei (Frontiers in Oncology, 2023)
40 papers that met the inclusion criteria were included in the systematic review. However, only 17 studies were used in the meta-analysis to determine the correlation between NLR, PLR and treatment response. We found that treatment with ICIs and monitoring of outcomes and adverse events using PLR and NLR parameters has been studied in different tumors. Our analysis showed that low NLR correlated with higher ORR (OR=0.62 (95%CI 0.47-0.81 p=0.001) and higher DCR (OR=0.23, 95%CI 0.14-0.36, p<0.001). Higher NLR predicted higher probability of PD (OR=3.12, 95%CI 1.44, 6.77, p=0.004). Similarly, low PLR corelated with higher ORR (OR= 0.69, 95%CI 0.5, 0.95 p=0.025). Generally, patients with low NLR and PLR were more likely to achieve clinical benefit and better response (p-value < 0.001). Meanwhile, patients with high ratios were more likely to progress (p-value < 0.005) although there was significant heterogeneity among studies. There was no significant publication bias observed.The study showed that high NLR and PLR either at baseline or during treatment is associated with poorer treatment outcome. Therefore these ratios can be utilized in clinical practice with other markers to determine treatment efficacy from immunotherapy